2009
DOI: 10.1136/bjsm.2009.065318
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of free play towards physical activity guidelines for New Zealand primary school children aged 7–9 years

Abstract: this study found activity levels were considerably lower than the recommended guidelines, and children were more active during school playtime compared to after school and weekends.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 25 publications
3
20
0
1
Order By: Relevance
“…Overall, children were slightly more sedentary and less active than on a weekday, without the marked peaks observed during the school days as has also been found in other studies 24 40 41. This change in activity at weekends may be a consequence of the different influences on children's activity at weekends including an increase in sedentary time spent using electronic devices 42.…”
Section: Discussionsupporting
confidence: 76%
“…Overall, children were slightly more sedentary and less active than on a weekday, without the marked peaks observed during the school days as has also been found in other studies 24 40 41. This change in activity at weekends may be a consequence of the different influences on children's activity at weekends including an increase in sedentary time spent using electronic devices 42.…”
Section: Discussionsupporting
confidence: 76%
“…One study was identified from each of New Zealand [26], Ireland [34] and Portugal [36] and one study had a combined sample from Bulgaria, Taiwan and the United States [40]. …”
Section: Resultsmentioning
confidence: 99%
“…These studies were grouped together as at ‘other locations’ [1113, 21, 2428, 30–37]. No studies investigating sedentary behaviors assessed behaviors when children were at after-school care, therefore all were considered ‘other locations’ ( n  = 9) [26, 3846]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have found that children are more active on weekdays (Duncan, Schofield & Duncan, 2006;Duncan, Al-Nakeeb, Woodfield & Lyons 2007;McGall, McGuigan & Nottle, 2011;Oliver, Schofield & Kilt, 2007;Owens et al, 2009;Riddoch, Mattocks et al, 2007). Research suggests that highly active children spend more time in physical activity before school, during class, lunch and after school (Rowlands, Pilgrim & Eston, 2008).…”
Section: Environmental Differencesmentioning
confidence: 97%